The prevalence of anxiety and depression symptoms among sexually abused adolescents in Iceland : the importance of protective factors - Bryndís Ósk Birgisdóttir 1994- (2019)
The purpose of this study was to analyze the prevalence of anxiety and depression symptoms among sexually abused adolescents and the moderating effects of protective factors, such as self-esteem and social support. The data used in this study were collected in 2014 by Icelandic Centre for Social Research and Analysis (ICSRA). Participants were 2509 Icelandic elementary students in 8th, 9th, and 10th grade and there were 1226 males and 1258 females. The results showed that depression and anxiety symptoms were higher if adolescents were sexually abused compared to those who were not sexually abused. Self-esteem and parental support had moderating effect on the relationship between CSA and symptoms of anxiety and depression whereas higher self-esteem and higher parental support had stronger effect on symptoms of depression and anxiety for sexually abused adolescents rather than those who were not sexually abused. Clinical psychologist could use these results to enhance their treatment with sexually abused adolescents and their parents, whereas good and supportive relationship from their parents is important for their mental health. Keywords: child sexual abuse, anxiety, depression, self-esteem, parental support Tilgangur þessarar rannsóknar var að skoða algengi einkenna kvíða og þunglyndis meðal unglinga eftir kynferðisofbeldi og áhrif verndandi þátta, eins og sjálfstraust og foreldrastuðnings á sambandið milli kynferðisofbeldis og einkenna þunglyndis og kvíða. Gögnin fyrir rannsóknina voru fengin frá Rannsóknum og Greiningu. Þátttakendur voru 2509 íslenskir grunnskólanemendur í 8, 9 og 10 bekk og þar af voru 1226 drengir og 1258 stúlkur. Niðurstöðurnar sýndu að einkenni þunglyndis og kvíða voru hærri hjá þeim sem höfðu upplifað kynferðisofbeldi samanborið við þá sem höfðu ekki upplifað slíka reynslu. Sjálfstraust og foreldrastuðningur höfðu mótandi áhrif á sambandið milli kynferðisofbeldis og einkenna kvíða og þunglyndis, þar sem hærra sjálfstraust og meiri foreldrastuðningur hafði sterkari áhrif á einkenni ...